2015
DOI: 10.1111/fcp.12130
|View full text |Cite
|
Sign up to set email alerts
|

Animal models to evaluate anti‐atherosclerotic drugs

Abstract: Atherosclerosis is a multifactorial condition characterized by endothelial injury, fatty streak deposition, and stiffening of the blood vessels. The pathogenesis is complex and mediated by adhesion molecules, inflammatory cells, and smooth muscle cells. Statins have been the major drugs in treating hypercholesterolemia for the past two decades despite little efficacy. There is an urgent need for new drugs that can replace statins or combined with statins. The preclinical studies evaluating atherosclerosis requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…New Zealand white rabbits have been widely used to evaluate the kinetics of lipoproteins [13,28,29,30,31,32,33,34] due to their metabolic similarities with humans, which are absent in other animal species such as rats and mice [35]. Previously, we reported that the HDL structure is importantly modified in the setting of exogenous hypercholesterolemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand white rabbits have been widely used to evaluate the kinetics of lipoproteins [13,28,29,30,31,32,33,34] due to their metabolic similarities with humans, which are absent in other animal species such as rats and mice [35]. Previously, we reported that the HDL structure is importantly modified in the setting of exogenous hypercholesterolemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pigs, which can spontaneously form atherosclerosis, provide a more representative animal model for studying dyslipidemia and atherosclerosis [7,8]. The physiological and anatomical aspects of pigs in lipid metabolism, cardiovascular metabolism and digestion are very similar to those in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A major obstacle in the assessment of food-based dietary patterns on the development of CAD is the lack of appropriate animal models. Rodents are a poor translational model because they have lipoprotein profiles that are dissimilar to humans and, unless genetically modified or fed extreme diets, rarely develop atherosclerosis (12–14). Pigs offer a more representative animal model (12–15).…”
Section: Introductionmentioning
confidence: 99%
“…Rodents are a poor translational model because they have lipoprotein profiles that are dissimilar to humans and, unless genetically modified or fed extreme diets, rarely develop atherosclerosis (12–14). Pigs offer a more representative animal model (12–15). Their cardiovascular anatomy and disease pathogenesis are like that of humans, and they are omnivorous, making them amenable to the study of food-based dietary patterns (12, 14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation